Mesenchymal Stem Cells Inhibits Migration and Vasculogenic Mimicry in Nasopharyngeal Carcinoma Via Exosomal MiR-125a - Wan, Fangzhu; Zhang, Haojiong; Hu, Jiyi; Chen, Li; Geng, Shikai; Kong, Lin; Lu, Jiade J. (Frontiers in Oncology, 2022)
Vasculogenic mimicry (VM) is a kind of tumor vasculature providing blood supply for tumor growth, and the formation of VM is independent of vascular endothelial cells. Instead, VM structures are formed by differentiated tumor cells such as nasopharyngeal carcinoma cells. Recently, studies have shown that anti-angiogenic therapy failed to improve the overall survival for patients, namely, nasopharyngeal carcinoma patients. The existence of VM structure is probably one of the reasons for resistance for anti-angiogenic therapy. Therefore, it is important to study the mechanism for VM formation in nasopharyngeal carcinoma. In this study, the bioinformatic analysis revealed that microRNA-125a-3p (miR-125a) was highly expressed in normal nasopharyngeal epithelial tissue than in nasopharyngeal carcinoma. An in vitro study demonstrated that miR-125a plays an inhibitory role in nasopharyngeal carcinoma cell migration and VM formation, and further studies confirmed that TAZ is a direct downstream target for miR-125a. On this basis, we artificially engineered human mesenchymal stem cells (MSCs) to generate exosomes with high miR-125a expression. Treatment with these miR-125a-over-expressing exosomes attenuated the migration and VM formation in nasopharyngeal carcinoma cells. In addition, the inhibitory role of these exosomes on VM formation and migration in nasopharyngeal carcinoma was also confirmed in vivo. Overall, the current study shows that MSCs can be utilized to generate exosomes with high miR-125a level, which could be therapeutic nanoparticles targeting VM formation in nasopharyngeal carcinoma and used as a complement to anti-angiogenic therapy in the future.